A Measurement System for Shape Memory Alloy Wire Actuators. (November 2015) - Daudpoto, Jawaid; Dehghani-Sanij, Abbas; Richardson, Robert
In this paper, an experimental set-up for the measurement of actuation properties of shape memory alloy wire actuators is presented. A test rig is designed and developed to characterise shape memory alloy wire actuators. The test rig is equipped with force, displacement and temperature sensors. The test rig is validated by measuring the strain of bi-atomic nickel–titanium shape memory alloy actuators by supplying various actuation currents. At 420 mA, the 0.15-mm-diameter nickel–titanium actuators underwent 3.25% strain which lies within the guideline range (3%-4%) reported by the manufacturer of the actuators.